STRATEGI KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA ORGANISASI YANG INOVATIF DI SMP AL-AZHAR KOTA BANJAR: Kepemimpinan Kepala Sekolah; Budaya Organisasi; Inovasi; Transformasi Pendidikan - Ismail, Feiby; Rahmawati, Ima; Muwaffiq, Muhamad Alwi; Ihsan, Muzhir (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2025)
This study aims to describe and analyze the principal's leadership strategy in building an innovative organizational culture at Al-Azhar Junior High School, Banjar City. The approach used is qualitative with a case study design. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation studies. The results of the study show that school principals apply a transformational leadership style characterized by the development of a shared vision, teacher empowerment, and the creation of a collaborative environment. The main strategies used include strengthening the learning community, the use of digital technology, and effective and empathetic communication. The principal also succeeded in fostering innovative values such as openness, courage to take risks, and a commitment to continuous learning. Despite facing challenges such as resistance to change and limited resources, principals are able to create an organizational climate that is supportive of innovation. These findings affirm the importance of visionary leadership in shaping an organizational culture that is adaptive and responsive to changes in education policy